Options for increasing tax - Roantree, Barra (The Institute for Fiscal Studies, 2015)
The UK’s public finances are still in a weakened state. In 2015–16, the government expects to borrow 3.6% of national income over and above the borrowing that can be expected to disappear as the economy recovers, leading all three main political parties to commit to further fiscal consolidation over the next parliament, albeit to varying extents. As discussed in Chapter 1, the plans set out in the Autumn Statement imply 98% of the remaining fiscal consolidation (from now until 2019–20) coming from net spending cuts and 2% coming from net tax rises. To date, none of the parties has proposed significant further net tax rises. But in the absence of tax rises all the parties’ targets imply a combination of large cuts to spending on social security benefits (discussed in Chapter 9) and/or public services (discussed in Chapter 7). To limit the scale of such cuts, it would not be surprising if an incoming government were to contemplate raising taxes following the May 2015 general election. Nor would such a scenario be at all unusual. As Figure 10.1 shows, there is a tendency for elections to be followed by substantial tax increases: every general election since 1992 has been followed within 12 months by an announcement of more than £5 billion (in 2015–16 terms) of net tax rises. This chapter discusses a wide range of options that a future tax-raising government might consider, assessing how much revenue they would raise, who would bear the burden and what economic effects they might have. We draw on the findings of the Mirrlees Review of taxation1 to consider whether the reforms would move the UK towards a more rational tax system. Ultimately, however, we cannot advocate any particular tax-raising measures: who should bear the burden of fiscal consolidation is a value judgement we are not in a position to make. Which, if any, reforms to pursue would depend on a government’s distributional goals and wider priorities. By way of background, Section 10.2 briefly outlines the level and composition of government revenues. Section 10.3 examines increases in the biggest taxes that would affect large sections of society. Section 10.4 focuses on tax increases that target the well- off and Section 10.5 turns to the potential for raising revenue by scaling back tax reliefs to broaden the base on which taxes are levied. The final set of measures discussed, in Section 10.6, are ‘temptations to resist’ that would increase revenues in particularly damaging ways. Section 10.7 draws all of these strands together, summarises the revenue and distributional effects of the different options and concludes. Unless otherwise stated, in this chapter reforms’ revenue effects are annual and relate to 2015–16. Where full-year costings are available only for other years, they are adjusted in line with nominal growth in national income to express them in 2015–16 terms.
The IFS Green Budget: February 2015
PUBLISHED
Keywords: Inclusive Society